Effect of excess air on polycyclic aromatic hydrocarbons removal from petroleum sludge using thermal treatment with additives - Pakpahan,E.N. (National Institute of Science Communication and Information Resources (NISCAIR), 2015)
© 2015 Scientific Publishers. All rights reserved. Petroleum sludge contains polycyclic aromatic hydrocarbons (PAH) which are hazardous compounds due to their toxic and carcinogenic-mutagenic characteristics. The United States Environmental Protection Agency has identified 16 of these compounds as priority pollutants. This study evaluates the effectiveness of excess air addition in thermal removal of priority PAH from petroleum sludge treated in a rotary-drum electric heater at 650°C with Ca(OH)2 (1 mole) + NaHCO3 (1 mole) (1:1) additives. The concentrations of PAH in flue gas and residue phases were determined using Gas Chromatography-Mass Spectrometry (GC-MS). The samples were extracted with acetonitrile by ultra-sonication prior to GC-MS analysis. The concentrations of 2-3 ring PAH, 4-6 ring PAH, suspect carcinogenic PAH, ΣPAH and ΣTEF were also determined. Excess air addition was found to be instrumental in PAH removal.